The Collateral for Land Rights Transferred into Selling and Buying Objects - Mas Rara Tri Retno Herryani (UNISSULA, 2023)
The purpose of this research is to analyze collateral benefits, mortgage security institution, principles of security law, the problem of good faith in debt agreement, legal protection for debtors if debt collateral objects are transferred into sale and purchase objects. The granting of credit to the debtor should be bound by a principal agreement and an accessory agreement for the collateral provided, but it happens that the debtor is bound by a principal agreement and a sale and purchase bond agreement along with a power of sale. When the debtor defaults, the name will be changed to the name of the creditor. The research method in this research is normative juridical research method, and the approach method used is Statute Approach, and Conceptual Approach. The result of the research is that debtors who have obtained debts from creditors and submitted land rights collateral, should be bound by an accesoir agreement, namely a mortgage right as in Act No. 4 of 1996, instead of binding the sale and purchase and power of sale. If this is still done by the creditor, the debtor can take a settlement method, namely: Alternative Dispute Resolution; Court.